2003
DOI: 10.1021/ic020733f
|View full text |Cite
|
Sign up to set email alerts
|

The CsLnMSe3 Semiconductors (Ln = Rare-Earth Element, Y; M = Zn, Cd, Hg)

Abstract: CsLnCdSe(3) (Ln = Ce, Pr, Sm, Gd, Tb, Dy, Y) and CsLnHgSe(3) (Ln = La, Ce, Pr, Nd, Sm, Gd, Y) have been synthesized at 1123 K. These isostructural materials crystallize in the layered KZrCuS(3) structure type in the orthorhombic space group Cmcm and are group X extensions of the previously characterized Zn compounds. The structure is composed of two-dimensional [LnMSe(3)] layers that stack perpendicular to [010] and are separated by layers of face- and edge-sharing CsSe(8) bicapped trigonal prisms. Because the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 46 publications
9
71
2
Order By: Relevance
“…4c. The intersection of the least-squares lines of baseline and band edge [28] lead to an optical band gap of 2.37 eV. This value is consistent with the reddish-yellow color of the compound and agrees well with theory.…”
Section: Absorbance Spectrumsupporting
confidence: 85%
See 2 more Smart Citations
“…4c. The intersection of the least-squares lines of baseline and band edge [28] lead to an optical band gap of 2.37 eV. This value is consistent with the reddish-yellow color of the compound and agrees well with theory.…”
Section: Absorbance Spectrumsupporting
confidence: 85%
“…Electronic structure calculations indicate that NaLiCdS 2 is semiconducting (see below). In order to determine the nature of the transition at about 2.4 eV the scaled absorption value and the crystal thickness were used to calculate the absorption coefficient a [28]. Plots of (ahn) 2 vs. hn (Fig.…”
Section: Absorbance Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…4. Based on the diffuse reflectance measurement and the electronic structure calculation, the Sn 2 SiS 4 should possess an indirect band gap of about 2.00 eV [41,42].…”
Section: Experimental Band Gapmentioning
confidence: 99%
“…Both from experiment and first-principles electronic structure calculations, it is found that the band gaps of the ALnMQ 3 materials (A ϭ Rb, Cs; Ln ϭ rare-earth metal; M ϭ Mn, Zn, Cd, Hg) can be tuned through simple chemical substitution of Ln, M, or Q [5Ϫ7]. For some of these compounds, there is also a slight dependence of band gap on crystal orientation [5,8]. Most of these compounds show Curie-Weiss behavior [7], except for the compounds Ln ϭ Yb/M ϭ Mn, Zn that show magnetic transitions at temperatures below ϳ10 K. Thus these ALnMQ 3 compounds are a new class of magnetic semiconductors with tunable band gaps that show potential applications in magnetic storage devices [9,10] and photonic devices such as optical waveguides [11], optical filters [12], spontaneous emitters [13], and photon traps [14].…”
Section: Introductionmentioning
confidence: 99%